Permodelan Efisiensi Smart Home Menggunakan Mobile Programming - Suci Sri Utami Sutjipto; Septian Cahyadi; Anton Sukamto; Denny Dolok (Jurnal Informatika Kesatuan, 2021)
The utilization of Indonesia's electricity consumption every year continues to increase in line with national economic growth. This situation is a general description of every developing country, where the supply of electricity is not the fulfillment of the real needs of the whole but rather the ability to generate and distribute electricity to the community. Indonesia has a target to provide lighting or electricity to all citizens by 2020 or an electrification ratio of 100%, and by 2019, the government said the realization of the electrification ratio had reached 98.89%. This means that we have almost reached our target. To achieve this ambitious target, efforts have been made, including developing electricity infrastructure, such as solar power plants, to the 3T (underdeveloped, frontier, and outermost) areas using the Special Allocation Fund (SAF). The existence of a smart home (smart home) allows users to remotely control parts of the house and set a schedule for activated smart home devices to help control costs and save more energy while providing added convenience and save time. So that it can save household electricity consumption and save energy. Mobile-based smart home efficiency modeling, based on temperature sensors, human movement, and light intensity sensors using a mobile-based microcontroller to help save electricity use and reduce global warming. By carrying out this research, it can facilitate community activities in controlling automation in smart homes to save electrical energy and reduce global warming. The Hardware Programming method is an approach method for designing the tools used. Kata Kunci: Mobile programming, Hardware Programming, Smart home.